Parenting style of father as a factor of socio-psychological adaptation of adolescents - Mandzyk, T. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article considers the problem of parenting styles of father in subjective teenagers’ perception, its importance for the development of socio- psychological adaptation and the dominant type of teen attitudes toward others in the communication sphere. Also we detailed analyzed the importance of fathers in a child’s upbringing and the influence of different models of his behavior on the formation personality traits of adolescents.